2021
DOI: 10.1093/nargab/lqab018
|View full text |Cite
|
Sign up to set email alerts
|

ResistoXplorer: a web-based tool for visual, statistical and exploratory data analysis of resistome data

Abstract: The study of resistomes using whole metagenomic sequencing enables high-throughput identification of resistance genes in complex microbial communities, such as the human microbiome. Over recent years, sophisticated and diverse pipelines have been established to facilitate raw data processing and annotation. Despite the progress, there are no easy-to-use tools for comprehensive visual, statistical and functional analysis of resistome data. Thus, exploration of the resulting large complex datasets remains a key … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Values were compared and tested using t-Test and p-value of < 0.05 was considered statistically significant. Additional resistance gene statistical analysis was performed using ResistoXplorer [ 30 ]. In brief, the summary gene detection data from Abricate was utilised together with metadata and a resistance gene key for uploading to ResistoXplorer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values were compared and tested using t-Test and p-value of < 0.05 was considered statistically significant. Additional resistance gene statistical analysis was performed using ResistoXplorer [ 30 ]. In brief, the summary gene detection data from Abricate was utilised together with metadata and a resistance gene key for uploading to ResistoXplorer.…”
Section: Methodsmentioning
confidence: 99%
“…ALDEx2, an ANOVA-like differential expression tool, was utilised with the Wilcoxon test to determine ranking of resistance gene abundance with a Monte Carlo number set at the default of 64 samples. ALDEx2 estimates variation within samples using Monte-Carlo instances and using centered log-ratio transformation [ 30 , 31 ]. Further identification of contigs with AMR genes was performed using the NCBI Basic Local Alignment Tool (BLAST) [ 32 ], using the default parameters and standard nucleotide collection (nr/nt).…”
Section: Methodsmentioning
confidence: 99%
“…RStudio (Version V4.0.3) was used for graphical representation using the libraries “ ggplot2 ,” “ reader ,” and “ esquisse .” Additionally, we used the web‐based tool ResitoXplorer 22 to visualize and generate a statistical analysis of the composition profiling, clustering analysis, differential abundance testing, and integrative analysis. The filtration process removed low‐quality or non‐informative ARGs to improve the statistical tests using ResitoXplorer's default parameters (low count and low variance filters).…”
Section: Methodsmentioning
confidence: 99%
“…RStudio (Version V4.0.3) was used for graphical representation using the libraries "ggplot2," "reader," and "esquisse." Additionally, we used the web-based tool ResitoXplorer 22 to visualize and generate a F I G U R E 1 Study design and antibiotic-resistant genes identified in fecal samples from patients who received eradication therapy against H. pylori. (A) Treatment groups, time points of analysis, and number of samples studied.…”
Section: Statistical and Integrative Analysismentioning
confidence: 99%
“…Genes that confer resistance to fusidic acid, antibacterial free fatty acid, aminocoumarin, acridine dye, elfamycin, glycylcycline, isoniazid, mupirocin, nitrofuran, nitroimidazole, nucleoside, pactamycin, polyamin, and rifamycin were herein classified as "others." All images and statistical analysis were performed using ResistoXplorer (http://www.resistoxplorer.no/; Dhariwal et al, 2021) online software. We assessed alpha and beta diversities to visualize how the different identified genes were related within and between groups, respectively.…”
Section: Basecalling and Resistome Constructionmentioning
confidence: 99%